A Mild and Highly Efficient Conversion of Arylboronic Acids into Phenols by Oxidation with MCPBA - Chen, Dong-Song; Huang, Jing-Mei (Synlett, 2013)
A mild and highly efficient synthesis of phenols from arylboronic acids in a H2O–EtOH (1:2) solution was achieved by using MCPBA as the oxidant at room temperature. Isotopical labeling studies had shown that the hydroxyl oxygen atom of the phenol might originate from the MCPBA.
Keywords: arylboronic acids; efficiency; MCPBA; oxidation; phenols